TPACK (Technological, Pedagogical, and Content Knowledge) untuk Peningkatan Profesionalisme Guru PAUD - Nurhayani, Nurhayani; Yuanita, Sri Kemala Sandi; Permana, Ayu Intan; Eliza, Delfi (Jurnal Basicedu, 2022)
The teachersâ€™ ability to apply technology in delivering learning materials is one of the factors to become a professional teacher. The purpose of this study was to analyze the framework of Technological Pedagogical and Content Knowledge (TPACK) in order to improve the professionalism of early childhood education teachers. The methodology of this research used the type of qualitative descriptive research. The respondents of this research were early childhood education teachers in Payakumbuh City. The data collection technique of this research was used interview, observation and documentation. From the result of this study, it can be concluded that the Technological Knowledge (TK) of early childhood education teachers is in â€œenoughâ€ category, Content Knowledge (CK) in the â€œgoodâ€ category, Pedagogical Knowledge (PK) in the â€œgoodâ€ criteria, Technological Content Knowledge (TCK) in â€œenoughâ€ criteria, Technological Pedagogical Knowledge (TPK) in â€œenoughâ€ criteria, Pedagogical Content Knowledge (PCK) teachers belong to â€œgoodâ€ and Technological Pedagogical and Content Knowledge (TPACK) early childhood education teachers in Payakumbuh City were on â€œenoughâ€ criteria.